2012
DOI: 10.1590/s0102-311x2012000400008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores de risco para asma em adolescentes de 13 a 14 anos do Município de Cuiabá, Mato Grosso, Brasil

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
(43 reference statements)
0
9
0
3
Order By: Relevance
“…There are similarities between the nasal and bronchial mucosa, and one of the most important concepts about nose-lung interactions is that there is a functional systemic link between the upper and lower airways. ( 25 ) In addition, among public school students, there was an improvement in the perception of milder symptoms of the disease-represented by the increase in the frequency of the response "no rhinitis-related impairment of daily activities"-and this might be contributing to more cases being treated and to a consequent decrease in the frequency of severe cases, a decrease that was found to be significant in this particular group.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…There are similarities between the nasal and bronchial mucosa, and one of the most important concepts about nose-lung interactions is that there is a functional systemic link between the upper and lower airways. ( 25 ) In addition, among public school students, there was an improvement in the perception of milder symptoms of the disease-represented by the increase in the frequency of the response "no rhinitis-related impairment of daily activities"-and this might be contributing to more cases being treated and to a consequent decrease in the frequency of severe cases, a decrease that was found to be significant in this particular group.…”
Section: Discussionmentioning
confidence: 89%
“…Some studies have demonstrated a parallel increase in the prevalences of asthma and rhinitis, whereas others have not. ( 25 ) In the ISAAC phase III, no consistent global temporal trend was identified in the prevalence of rhinoconjunctivitis among children. ( 26 , 27 ) …”
Section: Discussionmentioning
confidence: 99%
“…The studies carried out in Phases I and III of the ISAAC show a trend towards stabilization and even a decrease in the prevalence of asthma in adolescents in some localities. However, for the regions of Africa, India, Latin America, Northern Europe and Eastern Europe the expectation is for an increase 11 . In the study by Jucá et al 11 , the prevalence of active asthma was 19.1%.…”
Section: Discussionmentioning
confidence: 99%
“…However, for the regions of Africa, India, Latin America, Northern Europe and Eastern Europe the expectation is for an increase 11 . In the study by Jucá et al 11 , the prevalence of active asthma was 19.1%. In other locations in Brazil, results from the ISAAC Phase III study showed active asthma rates varying from 11.8% in Nova Iguaçu (Rio de Janeiro) to 30.5% in Vitória da Conquista, Bahia, Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire, along with data about asthma symptoms, contained information about the history of childbirth, breastfeeding, the nuclear family, diseases and immunizations, information about the home, type of food, and the children's anthropometric data. The instrument was also constructed based on a dissertation project (8) and was completed with the child's primary caregiver (mother, father, grandmother and / or aunt).…”
Section: Methodsmentioning
confidence: 99%